Role of International Actors in the Azerbaijan-Armenia Conflict over Nagorno-Karabakh - Atif ur Rahman; Mumtaz Hussain; Zubair Hussain (ASIAN Journal of International Peace & Security (AJIPS), 2021)
Nagorno-territory Karabakh’s is internationally recognized as an integral part of Azerbaijan, which controls the Armenian-ethnic population. The unresolved territorial dispute between two states, “Armenia and Azerbaijan,” over the Nagorno-Karabakh region is the most dangerous threat to the security of the South Caucasus and neighbouring states. The novel ceasefire agreement between Armenia and Azerbaijan was brokered unilaterally by Russia, with the major regional actors excluded. As a result, the Armenian masses were outraged, and the territory’s legal status remained ambiguous. For decades, the regional confrontation significantly altered geopolitical and geostrategic circumstances, as well as regional and non-regional actors’ efforts to reach a comprehensive resolution. In this context, Turkey has a favorable impact on the entire region as a transit energy state, serving as a bridge to the West due to its distinctive location. With the participation of major regional stakeholders, the frozen conflict can easily be transformed into a new cycle of violence. This research aimed to analyze the role of regional actors in the disputed region of Nagorno-Karabakh and explore their geopolitical and geostrategic interests of regional and great powers by using secondary sources of data and seeking a solution to the conflict.